Aerodynamic Performance of the Single-Stage Transonic Turbine With Different Reaction Degrees - Jia, Qiankun; Xu, Senpei; Sun, Peipei; Du, Wei (Frontiers in Energy Research, 2022)
A numerical method was used to investigate the reaction degree effects on the aerodynamic performance and flow structure of the single-stage transonic turbine. The SST-γ-θ turbulence model was employed to predict a transition for the boundary layer near the blade surface. This work utilized a public PW-E3 blade profile from NASA. Five different reaction degrees were adopted, corresponding to Ω=0.15, 0.27, 0.33, 0.44, 0.59. In addition, different off-design conditions were considered with three reaction degrees. The efficiency, profile pressure and high Mach number distributions were significantly associated with the reaction degrees. Results indicated that the highest efficiency point was observed at Ω= 0.33. The trailing edge shocks and the reflected waves were visible in the cascade channels. The Shock wave was easily detected in the stator channel at lower reaction degrees while it was displayed in a rotor with a higher reaction degree. When the reaction degree was increased, the high Mach number region was expanded in the rotor channels while it was reduced in stators. Besides, the highest efficiency points were also observed around π=1.5 for all operating conditions. Furthermore, the critical pressure ratio was discovered and the maximum mass flow rate gradually decreases as the reaction degree increases.